1998
DOI: 10.1159/000030908
|View full text |Cite
|
Sign up to set email alerts
|

Historical Note: Past, Present and Future of the Antiglobulin Test

Abstract: This is a review of two invited talks on the antiglobulin reaction on the occasion of the 50th Anniversaries of the International Blood Group Reference Laboratory, now at Bristol, and the National Blood Service, London, and coincidentally the 51st anniversary of the antiglobulin test! The first talk (as specially requested) is a very personal reminiscence of the discovery, with Rob Race and Arthur Mourant, of the antiglobulin test in blood group serology. The second talk traces developments in antiglobulin tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The history of the test has been reviewed recently by R.R.A. Coombs himself [1]. It has been reported that the gel test, a novel and promising method described by Lapierre et al [2], is as good or better than the conventional tube technique for demonstrating in vivo antibodies and/or complement coating red blood cells [3].…”
Section: Introductionmentioning
confidence: 99%
“…The history of the test has been reviewed recently by R.R.A. Coombs himself [1]. It has been reported that the gel test, a novel and promising method described by Lapierre et al [2], is as good or better than the conventional tube technique for demonstrating in vivo antibodies and/or complement coating red blood cells [3].…”
Section: Introductionmentioning
confidence: 99%
“…It was shortly before July 1945 that, according to Mourant (1983), Dr Coombs conceived the principle of the anti‐globulin reaction in a brilliant feat of intuition. Dr Coombs (1998) described a late night ride on an ill‐lit train from London to Cambridge during which he was pondering the nature of the incomplete antibodies attached to RBCs, with visions of Ehrlich's side‐chain theory running through his head. ‘In a flash I could see the globulin antibody on the red cells, and these cells should be agglutinated with an antibody to serum globulin, i.e.…”
Section: World War IImentioning
confidence: 99%
“…However, it was not until 1945, when Coombs showed that blood group antibodies could be demonstrated in serum or on sensitized RBCs, that the test was adopted by clinical laboratories. 1 The DAT is an essential test in the evaluation of autoimmune hemolytic anemia (AIHA). The DAT also has importance in the blood bank, where it is performed as part of the evaluation of hemolytic transfusion reactions.…”
mentioning
confidence: 99%